Unified rules of driver conduct on the territory of factories and logistics hubs: an international approach - Saniuta, Kostiantyn Oleksandrovych (Global Prosperity, 2025)
Abstract. The logistics and transport system is currently characterized by active development, which requires the involvement of new approaches to regulating certain aspects of road traffic. The purpose of the article is to analyze the potential of modern concepts of unification of the rules of behavior of drivers on the territory of manufacturing enterprises and logistics hubs in the context of the experience of the USA, the European Union countries and Ukraine. The study considers the categories of basic traffic rules (observance of road signs, markings, priority of movement and pedestrian safety, availability of necessary documents, etc.), as well as specific requirements for the territory of factories and logistics hubs, which take into account the specifics of transportation, cargo and rolling stock (speed limits, parking rules, prohibition of movement for certain categories of transport or in certain areas, etc.). Various requirements for the behavior of drivers on private territories in Europe, the USA, Ukraine, which are components of the strategies for ensuring road traffic in individual countries, are studied. New directions of digital optimization of driver behavior regulation in private areas are analyzed, complementary to modern demands of "smart" and "green" logistics, with the integration of individual elements of information and communication systems. It is substantiated that the implementation of unified standards of driver behavior in Ukraine faces a number of challenges, in particular, limited funding and insufficient managerial support. The promising potential of intelligent transport systems for improving the management of logistics and transport systems and developing responsible driving practices for traffic safety in closed areas is proven.